Imperatives and initiatives in education - Beddoe, Innocent B. (My University, 1992)
This paper identifies and briefly explores some of the structural changes needed in the national education system. The specific initiatives identified are discussed under the following headings: 1) Teacher education, 2) National norms, 3) Selection to enter secondary schools, 4) Adjusting the time frames, 5) Curriculum reform, 6) New institutions, 7) Waste avoidance, 8) An alternative shift system, and 9) Privatization in education.
Biennial Cross-Campus Conference on Education, 2nd, St. Augustine, Trinidad, 22-24 April, 1992
Keywords: educational organization